Politics, murder and love in an Italian family the Amendolas in the age of totalitarianisms - Bosworth, R. J. B. 1943- (Cambridge University Press, 2023)
What did it mean to live with fascism, communism, and totalitarianism in modern Italy? And what should we learn from the experiences of a martyred liberal democrat father and his communist son? Through the prism of a single, exceptional family, the Amendolas, R.J.B. Bosworth reveals the heart of twentieth-century Italian politics. Giovanni and Giorgio Amendola, father and son, were both highly capable and dedicated Anti-Fascists. Each failed to make it to the top of the Italian political pyramid but nevertheless played a major part in Italy's history. Both also had rich but contrasting private lives. Each married a foreign and accomplished woman: Giovanni, a woman from a distinguished German-Russian intellectual family; Giorgio, a Parisian working class girl, who, to him, embodied Revolution. This vivid and engaging biographical study explores the highs and lows of a family that was at the centre of Italian politics over several generations. Tracing the complex relationship between Anti-Fascist politics and the private lives of individuals and of the family, Politics, Murder and Love in an Italian Family offers a profound portrait of a century of Italian life